Tobacco Cessation and the Non-Allopathic Private Physician in India: A Survey in Navi Mumbai, India - Himanshu A Gupte; Vaibhav Thawal; Kripa Gopalan; Nilesh Chatterjee (Medsci Publications, 2020)
Background: Private non-allopathic practitioners are often the first point of medical care for low-income populations in India, and likely encounter a sizeable number of tobacco-users. While there is evidence that physicians' advice for tobacco cessation enhances quit rates among tobacco users, little is known about tobacco-cessation knowledge, attitudes and practices of private non-allopathic practitioners. Methods: A cross-sectional survey was conducted with non-allopathic private practitioners in Navi Mumbai, India. Results: Majority (92%) of the practitioners had not received any tobacco-cessation related training. Around 85% never ever-used tobacco; 82.5% said tobacco-use was harmful irrespective of age; and all respondents said tobacco products contained harmful chemicals. However, a third (32.5%) said smokeless tobacco was less harmful than smoking and 52.5% said tobacco-use was socially acceptable in India. Only 10% were aware of methods to measure nicotine dependence. Although 97.5% thought tobacco use was high among their patients, only 15% recorded individual tobacco-use in patient files; and a third (35%) referred the patient to cessation services. Female practitioners were more likely to refer for cessation (p=0.043). Conclusion: Only one in three practitioners referred tobacco-user patients to cessation or screening services indicating an urgent need for training and sensitization of private non-allopathic practitioners to increase the reach of tobacco-cessation services in India.